(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Gambling over the past centuries has evolved in terms of its expansion and form. Sports betting as one of the forms or components of gambling has grown globally over the years in the Americas, Europe, Asia and Africa. As a result, there is a reason to expect that gambling among university student may be more preponderant today than in previous years. Thus, the study explores the motivational factors towards sport betting and its widespread of problem gambling severity among university students. Descriptive survey design was adopted for the study. A fair representative sample size of 351 was determined through the Krejcie and Morgan minimum sample size determinant. Means, standard deviations, frequency counts, percentages were used in the analysis of the data. The study found that money was the leading motivational factor for university students’ sports gamblers. Thus, the study recommends the setting up of a ‘Gaming Research Unit’ in partnership with the Students’ Support Office (StuFSO) under the auspices of the university, to generate levies from gambling centres sited on and around the university’s campuses to help finance bursaries for average but needy students of the university who may be engaging in sport betting.